Coffee (Coffea arabica L.) by-Products as a Source of Carotenoids and Phenolic Compounds—Evaluation of Varieties With Different Peel Color - Esquivel, Patricia; Viñas, María; Steingass, Christof B.; Gruschwitz, Maike; Guevara, Eric; Carle, Reinhold; Schweiggert, Ralf M.; Jiménez, Víctor M. (Frontiers in Sustainable Food Systems, 2020)
Analysis of pulp and peels of Arabica coffee varieties with different external fruit color allowed the identification of 16 phenolic compounds using high-performance liquid chromatography with diode array detection and electrospray ionization multi-stage mass spectrometry (HPLC-DAD-ESI-MSn). Nine chlorogenic acids, three flavan-3-ols, the xanthone mangiferin, the flavonol rutin and two anthocyanins were tentatively identified and quantified. 5-O-Caffeoylquinic acid together with a putative (epi)catechin hexoside were the predominant phenolics detected in the coffee varieties analyzed in this work. Whereas, 3- and 4-caffeoylquinic acids, as well as 5-O-feruloylquinic acid were consistently found in higher quantities in the pulp than in the peels when individual varieties were compared, the opposite was found for the other phenolic compounds detected. Complementary, GC-MS after alkaline hydrolysis and trimethylsilylation permitted the identification of more than 30 constituents, including phenolic compounds and other benzenoids, caffeine, and diverse carboxylic acids. Detected anthocyanins were cyanidin-3-O-glucoside and cyanidin-3-O-rutinoside. Anthocyanin contents in orange-colored berries were lower than those in red fruits, while no anthocyanins were found in yellow-colored fruit. Among non-anthocyanin pigments, we found β-carotene and lutein in all varieties, along with other chloroplast-specific carotenoids in some accessions. In addition, saponification evidenced the presence of several xanthophyll esters. Both, chlorophyll a and b, were detected in the peels of all varieties, while only chlorophyll b was observed in the pulp. Thus, the color of yellow-peeled varieties is due to carotenoids, while that of orange and red-peeled varieties is due to both carotenoids as well as low and high levels of anthocyanins, respectively. Present results point out to the potential use of by-products of particular coffee varieties with differences in the external fruit color as a source of distinctive bioactive compounds, including anthocyanins and carotenoids, with health benefits.